94 A Pathway of Care for Patients with Parkinson's Disease in Cavan Monaghan Physiotherapy Department. (16th September 2019) - Sweeney, Mary; Creegan, Maura; Hall, Michelle; McGroarty, Donna; Graham, Jane
Abstract: Background: New European guidelines for the physiotherapy management of patients with Parkinson's disease were published in 2014. Following on from this publication it was decided to review the current physiotherapy service delivered to our patients with Parkinson's disease across both counties and develop a new pathway of care in line with the guidelines. Methods: A working group of physiotherapists was selected representing acute, primary care and disability services. This group initially met to review current practice. Once the service was evaluated, the group created a new assessment form for use across all physiotherapy services in both counties using validated outcome measurements as recommended in the guidelines. A training program was put in place to improve staff's skill level in using the new assessment form and treatment methods for this client group. It was decided that a yearly assessment would now be carried out on each patient with Parkinson's disease. Feedback was sought from therapists and any issues were addressed by the working group. As part of the pathway a new Parkinson's exercise group was created which runs twice yearly in both counties. Results: In 2018, 18 patients attended an exercise class in Cavan, 16 attended in Monaghan while yearly assessments were also completed. Patient feedback from the classes has been very positive and outcome measurements have shown an improvement. Patients enjoy the class setting immensely and physiotherapy staff feel their patients are benefiting from receiving a more prolonged period of intervention. Conclusion: This new pathway of care has been an effective and efficient way of treating patients with Parkinson's disease. It has led us to identify changes in disease progression in a more timely fashion. Outcome measurement is audited yearly to monitor quality of classes and benefit to patients. We will continue to highlight the pathway with new staff and monitor staff satisfaction with its use.